Water extraction on Mars for an expanding human colony. (November 2015) - Ralphs, M.; Franz, B.; Baker, T.; Howe, S.
Abstract: In-situ water extraction is necessary for an extended human presence on Mars. This study looks at the water requirements of an expanding human colony on Mars and the general systems needed to supply that water from the martian atmosphere and regolith. The proposed combination of systems in order to supply the necessary water includes a system similar to Honeybee Robotics' Mobile In-Situ Water Extractor (MISWE) that uses convection, a system similar to MISWE but that directs microwave energy down a borehole, a greenhouse or hothouse type system, and a system similar to the Mars Atmospheric Resource Recovery System (MARRS). It is demonstrated that a large water extraction system that can take advantage of large deposits of water ice at site specific locations is necessary to keep up with the demands of a growing colony.